Harī Pottā to kenja no ishi = Harry Potter and the philosopher's stone - Rowling, J. K.; Matsuoka, Yūko.; Schlesinger, Dan; Mardigian Endowment, 2008. (Tokyo : Say-zan-sha, 1999)
Harry Potter thinks he is an ordinary boy until he is rescued by an owl, taken to Hogwarts School of Witchcraft and Wizardry, learns to play Quidditch and does battle in a deadly duel. The reason: Harry Potter is a wizard.
American title: Harry Potter and the sorcerer's stone.
Mode of access: Internet.
Keywords: Potter, Harry -- (Fictitious character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; England -- Juvenile fiction